TRANSFORMING EDUCATIONAL MANAGEMENT THROUGH HYFLEX LEARNING TO FOSTER 21ST-CENTURY SKILLS IN SOCIETY 5.0 - Rizqi Nur Afifah; Fawzul Arifin; Anastasia Arta Uli (Program Studi Manajemen Pendidikan, 2025)
Educational management, often narrowly perceived as classroom discipline and administrative procedures, can be redefined as a human-centered approach to foster 21st-century skills in the era of Society 5.0. This study employs a Systematic Literature Review (SLR) of research published between 2020 until 2025 to identify effective practices in nurturing students’ critical thinking, creativity, collaboration, and communication. The findings reveal that strategies such as project-based learning, assigning clear roles within teams, providing constructive feedback, and integrating synchronous-asynchronous interactions in Hyflex learning environments significantly enhance learning outcomes. Moreover, attention to student well-being is essential for sustaining motivation and engagement. These practices illustrate that educational management is not limited to control and administration but serves as a framework for holistic human development. The study concludes that educators and schools should embrace the role of facilitators who not only prepare learners to navigate rapid global changes but also contribute to the realization of Sustainable Development Goal 4 (Quality Education).